The effect of azygos vein preservation on postoperative complications after esophageal atresia repair: Results from the Turkish Esophageal Atresia Registry - KIYAN, GÜRSU (W.B. Saunders, 2020)
Aim: Preservation of the azygos vein (AV) maintains normal venous drainage of the mediastinum and decreases postoperative congestion. The modification of esophageal atresia (EA) repair by preserving AV may prevent postoperative complications and may lead to better outcomes. The data from the Turkish Esophageal Atresia Registry (TEAR) were evaluated to define the effect of AV preservation on postoperative complications of patients with EA. Methods: Data from TEAR for a period of five years were evaluated. Patients were enrolled into two groups according to the preservation of AV. Patients with divided (DAV) and preserved AV (PAV) were evaluated for demographic and operative features and postoperative complications for the first year of life. The DAV and PAV groups were compared according to the postoperative complications, such as fistula recanalization, symptomatic strictures, anastomotic leaks, total number of esophageal dilatations, and anti-reflux surgery. In addition, respiratory problems, which required treatment, were compared between groups. Results: Among 502 registered patients; the data from 315 patients with the information of AV ligation were included. The male female ratio of DAV (n = 271) and PAV (n = 44) groups were 150:121 and 21:23, respectively (p > 0.05). The mean body weight, height, gestational age, and associated anomalies were similar in both groups (p > 0.05). The esophageal repair with thoracotomy was significantly higher in DAV group, when compared to the PAV group (p < 0.05). The rates of primary anastomosis and tensioned anastomosis were similar in both groups (p > 0.05). There was no difference between DAV and PAV groups for anastomotic leaks, symptomatic anastomotic strictures, fistula recanalization, and the requirement for anti-reflux surgery (p > 0.05). The rate of respiratory problems, which required treatment, was significantly higher in the DAV group (p < 0.05) Conclusion: The data in the TEAR demonstrated that preserving the AV during EA repair led to no significant advantage on postoperative complications, with exception of respiratory problems. AV should be preserved as much as possible to maintain a normal mediastinal anatomy and to avoid respiratory complications. © 2020
Keywords: Anastomotic strictures; Azygos vein; Complications; Esophageal atresia; Tracheoesophageal fistula